Conversations with RBG : Ruth Bader Ginsburg on life, love, liberty, and law - Rosen, Jeffrey, 1964-; Ginsburg, Ruth Bader (Henry Holt and Company, 2019)
This is a remarkable and unique book, an informal portrait of Justice Ginsburg, drawing on a series of her conversations with Rosen, starting in the 1990s and continuing through the Trump era. Rosen, a veteran legal journalist, scholar, and president of the National Constitution Center, shares with readers the justice's observations on a variety of topics, and her intellect, compassion, sense of humor, and humanity shine through.